Kontribusi Kompetensi Sosial Guru dalam Membentuk Karakter Siswa - Mazrur, Mazrur; Surawan, Surawan; Yuliani, Yuliani (CV. Creative Tugu Pena, 2022)
The purpose of writing this article is to analyze the teacher's social contribution in shaping students' character. Social competence possessed by a teacher here is very important, because if a teacher is able to apply these social competencies, especially in the school environment and students, then directly a teacher has instilled and nurtured students to have better character. With regard to the social competence of Islamic Education teachers in shaping the character of students in schools, Islamic education teachers to have social competence in approaching their students, teachers must of course pay attention to how to communicate and interact with students and must set a good example for students who have good character less can be formed with the approach already owned by islamic education teachers. Keywords: Teacher Social Competence, Developing Students Characters, Teachers Competence